A Study on Rural Youth's Shopping Preferences towards Mobile Phones and Personal Computers - Gowda, Kavitha R.; Mathews, Soney (2015)
A major portion of India that lives in villages has undergone a remarkable incremental change in many areas like, improved literacy rates, infrastructure, transportation, increased industrialization, reformed government policies to enhance status and livelihood of villagers. As result of this, even villager's purchasing power has increased, which can be noticed from success stories of FMCG providers for the target rural market. With many technological innovations that have been noticed in the mobile manufacturer and service provider and a need for computer in urban areas, rural youth is not an exception. This study is an attempt to understand the need for computer and mobile phones in rural youth and thus conclude on prospective market for the shopping goods.